3D Printed Cartilage‐Like Tissue Constructs with Spatially Controlled Mechanical Properties. (21st October 2019) - de Melo, Bruna A. G.; Jodat, Yasamin A.; Mehrotra, Shreya; Calabrese, Michelle A.; Kamperman, Tom; Mandal, Biman B.; Santana, Maria H. A.; Alsberg, Eben; Leijten, Jeroen; Shin, Su Ryon
Abstract: Developing biomimetic cartilaginous tissues that support locomotion while maintaining chondrogenic behavior is a major challenge in the tissue engineering field. Specifically, while locomotive forces demand tissues with strong mechanical properties, chondrogenesis requires a soft microenvironment. To address this challenge, 3D cartilage‐like tissue is fabricated using two biomaterials with different mechanical properties: a hard biomaterial to reflect the macromechanical properties of native cartilage, and a soft biomaterial to create a chondrogenic microenvironment. To this end, a bath composed of an interpenetrating polymer network (IPN) of polyethylene glycol (PEG) and alginate hydrogel (MPa order compressive modulus) is developed as an extracellular matrix (ECM) with self‐healing properties. Within this bath supplemented with thrombin, human mesenchymal stem cell (hMSC) spheroids embedded in fibrinogen are 3D bioprinted, creating a soft microenvironment composed of fibrin (kPa order compressive modulus) that simulate cartilage's pericellular matrix and allow a fast diffusion of nutrients. The bioprinted hMSC spheroids present high viability and chondrogenic‐like behavior without adversely affecting the macromechanical properties of the tissue. Therefore, the ability to locally bioprint a soft and cell stimulating biomaterial inside of a mechanically robust hydrogel is demonstrated, thereby uncoupling the micro‐ and macromechanical properties of the 3D printed tissues such as cartilage. Abstract : In this work, 3D bioprinting technology is used to develop a biomimetic cartilage‐like tissue with near‐paradoxical mechanical properties, being soft at the cellular level, due to the soft bioink composed of human bone marrow mesenchymal stem cells in the form of spheroids embedded in fibrinogen, and the stiff polyethylene glycol and alginate bath, showing great potential for cartilage regeneration studies.